Timing Game: Development of a Game for Temporal Perception Research - Teixeira, Alan Floriano; Gois, João Paulo; Brandão, André Luiz (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2025: Anais Estendidos do XXIV Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames_estendido.2025.11367, 2025)
Introduction: Temporal perception tasks are traditionally repetitive and time-consuming, often reducing participant engagement and affecting data quality in cognitive research. Serious Games offer a promising alternative to increase engagement while preserving scientific rigor. Objective: This paper presents the development of the Timing Game, a Serious Game that adapts temporal perception research into mobile-friendly and engaging minigame formats. Methodology or Steps: The development process involved iterative game design, expert consultation in cognitive science, and user feedback. Two gameplay modes were implemented: (1) Arcade Mode, focusing on isolated temporal tasks, and (2) Story Mode, embedding tasks within a narrative framework. Results: The game demonstrated high user engagement, suggesting improved data quality for temporal perception research. The source code is publicly available to encourage further scientific use and adaptation.